First report on genetic structure of Lobocheilos rhabdoura (Fowler, 1934) (Labeoninae, Cyprinidae) in Thailand: Insight the basic snowledge for fish breeding - Kentachalee, Naruemon; Pinthong, Krit; Tongnunui, Sampan; Tanomtong, Alongklod; Juntharat, Sitthisak; Supiwong, Weerayuth (Food Agricultural Sciences and Technology, 2023)
Lobocheilos rhabdoura is a fish of the genus Lobocheilos in the family Cyprinidae. It is popular as an ornamental fish in Thailand and is important to fisheries and the economy. Chromosomes and chromosome markers of this species were studied by conventional staining and NOR-banding techniques. Ten male and ten female specimens were collected from the Meklong Basin, Kanchanaburi Province. The chromosomes were directly prepared from kidney tissues. The results showed that diploid chromosome was 2n = 50 and the fundamental number (NF) was 90 in all specimens. The structure karyotype consisted of 10 metacentric, 18 submetacentric, 12 acrocentric and 10 telocentric chromosomes; 10m + 18sm + 12a + 10t in both sexes without morphologically differentiated sex chromosomes. NOR positive markers were observed in regions adjacent to telomere of long arm of the largest submetacentric chromosome pair. This study provides basic knowledge of the genetic structure of this species and this basic knowledge that can be applied for breeding of ornamental fish in the future.